Role of TNF-α, IL-1β and IL-6 in the local tissue damage induced by Bothrops asper snake venom: an experimental assessment in mice - Chaves Mora, Fernando (2005)
The role of the cytokines TNF-α, IL-1β and IL-6 in the acute local pathological effects induced by Bothrops asper snake venom was assessed in mice. Intramuscular injection of this venom induced increments in IL-1β and IL-6 in muscle, but no elevations of TNF-α were detected. Pentoxifylline (PTX), a methylxanthine derivative that inhibits the synthesis of TNF-α, and antibodies against these three cytokines were used to assess the role of these cytokines in venom-induced effects. As a control, PTX pretreatment was effective at abrogating lethality and serum TNF-α increments in mice subjected to endotoxemia induced by injection of Escherichia coli lipopolysaccharide, although it did not affect the increment in IL-1β and IL-6 in such endotoxic model. PTX failed to reduce lethality, hemorrhage, myonecrosis, dermonecrosis and edema induced by B. asper venom. Moreover, pretreatment with anti-cytokine antibodies was also ineffective at reducing venom-induced myonecrosis and hemorrhage. It is concluded that TNF-α, IL-1β and IL-6 do not have a significant role in the pathogenesis of the acute local pathological effects induced by B. asper venom in mice, although this does not exclude the possibility that these cytokines play a role in other aspects of venom-induced local pathology, as well as in the reparative and regenerative responses that take place after the onset of tissue damage.